Introduction of CORC® wires: highly flexible, round high-temperature superconducting wires for magnet and power transmission applications. (2nd November 2016) - Weiss, Jeremy D; Mulder, Tim; ten Kate, Herman J; van der Laan, Danko C
Abstract: Conductor on Round Core (CORC ® ) technology has achieved a long sought-after benchmark by enabling the production of round, multifilament, (RE)Ba2 Ca3 O7− x coated conductors with practical current densities for use in magnets and power applications. Recent progress, including the demonstration of engineering current density beyond 300 Amm −2 at 4.2 K and 20 T, indicates that CORC ® cables are a viable conductor for next generation high field magnets. Tapes with 30 μ m substrate thickness and tape widths down to 2 mm have improved the capabilities of CORC ® technology by allowing the production of CORC ® wires as thin as 3 mm in diameter with the potential to enhance the engineering current density further. An important benefit of the thin CORC ® wires is their improved flexibility compared to thicker (7–8 mm diameter) CORC ® cables. Critical current measurements were carried out on tapes extracted from CORC ® wires made using 2 and 3 mm wide tape after bending the wires to various diameters from 10 to 3.5 cm. These thin wires are highly flexible and retain close to 90% of their original critical current even after bending to a diameter of 3.5 cm. A small 5-turn solenoid was constructed and measured as a function of applied magnetic field, exhibiting an engineering current density of 233 Amm −2 at 4.2 K and 10 T. CORC ® wires thus form an attractive solution for applications between 4.2 and 77 K, including high-field magnets that require high current densities with small bending diameters, benefiting from a ready-to-use form (similar to NbTi and contrary to Nb3 Sn wires) that does not require additional processing following coil construction.